Eksistensi Gerakan Idiologi Transnasional HTI Sebelum dan Pasca Pembubaran - Qohar, Abd; Hakiki, Kiki Muhamad (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2017)
This article attempts to explore the local development of Hizbut Tahrir Indonesia (HTI), especially in Lampung. The research focuses on the networks of HTI’s recruitment to maintain its identity. It also alludes how the existence of HTI withstands with its dissolution in the era of President Joko Widodo. The research concludes: Firstly, there are systematically some procedures to contend the politics of identity and HTI’s recruitment such as organizing the demonstrations, striving seminar and public discussion, media networks, approaching to the prominent figures and educational institutions, interpersonal recruitment, and halaqah (personal indoctrination). Secondly, there two possibilities of post-dissolution of HTI that would be executed, 1. The formation of new mass organization as the alternate of HTI. 2. To be new party or proceed to join the Islamic Party. They may search the parties that are ideologically identical or similiar to HTI’s ideology like PKS, PPP, PAN, PBB. This would be happened if they fail to scramble and to maintain its ideology in the form of new mass organization.